2013
DOI: 10.1162/leon_a_00562
|View full text |Cite
|
Sign up to set email alerts
|

The Sound of Movement Wearables: Performing UKIYO

Abstract: Chor eographic principles of composition are largely directed at the creation of movement and the temporal organization of moving bodies in space. Some choreographers (e.g. Sidi Larbi Cherkaoui) think of this process as "temporary drawings" [1]; others (e.g. William Forsythe) work with complexity theories in mind and develop spatial methodologies for bodily extensions into environments that negotiate the intervals between presence (states of being) and transmutable movement in multiple ways. In tanztheater, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…An important aspect of the project presented here was the impact that the wearable sound system had on audiences and performers during rehearsals and presentations. In line with reactions to previous performance projects developed using wireless sound systems, feedback from presentations with the body-worn system showed that sound wearable devices are very effective tools to establish a direct and close connection with audiences (Powell 2007; Birringer and Danjoux 2013: 232–4). Further studies with wearable sound devices should consider ways of assessing this impact in different kinds of performance scenarios by employing a suitable evaluation method such as tests with trained panels (Bech and Zacharov 2006: 112–17), context-methods surveys such as the ones proposed by Wilson and Harrison (Wilson and Harrison 2010b: 250) or perceptual studies exploring spatial features of electroacoustic music performance in concert halls (Lynch and Sazdov 2011; Sazdov 2011: 22–7).…”
Section: Discussion and Future Workmentioning
confidence: 53%
“…An important aspect of the project presented here was the impact that the wearable sound system had on audiences and performers during rehearsals and presentations. In line with reactions to previous performance projects developed using wireless sound systems, feedback from presentations with the body-worn system showed that sound wearable devices are very effective tools to establish a direct and close connection with audiences (Powell 2007; Birringer and Danjoux 2013: 232–4). Further studies with wearable sound devices should consider ways of assessing this impact in different kinds of performance scenarios by employing a suitable evaluation method such as tests with trained panels (Bech and Zacharov 2006: 112–17), context-methods surveys such as the ones proposed by Wilson and Harrison (Wilson and Harrison 2010b: 250) or perceptual studies exploring spatial features of electroacoustic music performance in concert halls (Lynch and Sazdov 2011; Sazdov 2011: 22–7).…”
Section: Discussion and Future Workmentioning
confidence: 53%
“…For a comprehensive delineation the design-inmotion method, see Danjoux 2017. Other publications on choreosonic wearables and kinetic atmospheres include Birringer 2013Birringer , 2017bBirringer and Danjoux 2009a, 2009bDanjoux 2014. 4 Earlier in the 1960s, and concerning the notion of media as extensions to the communication condition of the present body, sociologist Erving Goffman had discussed (analog) technologies such as microphones and other mechanical devices as "boosting devices"-to amplify and augment the naked senses (Goffman 1963, p. 14).…”
Section: Notesmentioning
confidence: 99%
“…But in our literature overview we did not find any projects that integrate interactive costumes. This is different in performance arts, where computational systems often relate to the performer's body [1,4,16,28]. The majority attaches technologies to the performer and generates audio feedback from movement [4].…”
Section: Interactive Theatre and Performance Artsmentioning
confidence: 99%
“…There are dozens of examples but many are technical demos [6,19], proofs of principle [3], or fashion prototypes [15] and art pieces [4,28]. Beyond these, the potential of computational clothing for specific applications still needs to be demonstrated; in particular we need to ensure that it can integrate into existing practices and infrastructures.…”
Section: Introductionmentioning
confidence: 99%